Models of the yield curve and the curvature of the implied forward rate function - Yallup, Peter J. (Journal of Banking & Finance, 2012)
We examine several alternative models of the UK gilt yield curve using daily data for the period 12 July 1996–10 February 2010. We select the best models according to two criteria: low out of sample errors in pricing bonds and low curvature of the implied forward rate curve function. We suggest additions to some of the models that significantly improve their performance. Some of the new models out perform those typically used by the central banks. In particular this paper suggests that the model used by the Canadian Central Bank which both outperforms other models and is particularly easy to estimate, is well suited to the UK gilt market.